The Synthetic Peroxisome Proliferator-Activated Receptor-γ Agonist Ciglitazone Attenuates Neuroinflammation and Accelerates Encapsulation in Bacterial Brain Abscesses - Kielian, Tammy (2008)
Brain abscesses result from a pyogenic parenchymal infection commonly initiated by Gram-positive bacteria such as Staphylococcus aureus. Although the host immune response elicited following infection is essential for effective bacterial containment, this response also contributes to the significant loss of brain parenchyma by necrosis that may be reduced by modulating the inflammatory response. Ciglitazone, a PPAR-γ agonist with anti-inflammatory properties, was evaluated for its ability to influence the course of brain abscess development when treatment was initiated 3 days following infection. Interestingly, abscess-associated bacterial burdens were significantly lower following ciglitazone administration, which could be explained, in part, by the finding that ciglitazone enhanced S. aureus phagocytosis by microglia. In addition, ciglitazone attenuated the expression of select inflammatory mediators during brain abscess development including inducible NO synthase, TNF-α, IL-1β, CXCL2, and CCL3. Unexpectedly, ciglitazone also accelerated brain abscess encapsulation, which was typified by the heightened expression of fibronectin and α-smooth muscle actin-positive myofibroblasts. Collectively, through its ability to attenuate excessive inflammation and accelerate abscess encapsulation, ciglitazone may effectively sequester brain abscesses and limit bacterial dissemination.